Investigation and Research on the Current Situation of Professionalization of Family Education Guidance in Kindergartens (Journal of Global Humanities and Social Sciences, 2024)
Kindergarten is not only the first step for children to enter society but also a bridge between families and social educational resources. Through professional educational guidance, kindergartens are not only able to continue and consolidate the family's educational philosophy but also to provide professional support for families and help parents better fulfill their parental responsibilities. Through an in-depth study of the importance of family education in the growth of young children, this paper discusses the role of kindergartens in family education, aiming to build a more complete family education support system, and jointly promote the comprehensive growth of children.